Application of good and correct hand washing and toothbrushing techniques to prevent infectious diseases through healthy living education - Nurhanifah, Dewi; Elsa Sabil, Siti (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2025)
Personal health is an important factor in preventing the spread of infectious diseases, especially through daily habits such as washing hands and brushing teeth. This Community Service (PkM) activity aims to improve people's understanding and skills in applying good and correct handwashing and toothbrushing techniques through healthy living education. The methods used include counseling, direct demonstrations, and practices guided by health workers. This activity targets school children and the general public who are vulnerable to diseases due to suboptimal personal hygiene. The results of the activity showed that there was an increase in the knowledge and skills of participants in applying the correct handwashing and toothbrushing techniques, which is expected to contribute to reducing the incidence of infectious diseases such as diarrhea, respiratory infections, and dental and oral diseases. With continuous education, public awareness of the importance of personal hygiene can increase, thereby creating a healthier and disease-free environment